IMPACTOS DA URBANIZAÇÃO NA GEOMETRIA HIDRÁULICA DE CANAIS FLUVIAIS DA BACIA HIDROGRÁFICA DO RIO CASCAVEL, GUARAPUAVA/PR - Oliveira, Éderson Dias de (2011)
The study aimed to identify the impacts of urbanization in the morphology of Guarapuava waterways in the Rattlesnake River basin. The discussions were focused on five main methodological aspects being:measurement of geometric aspects of open and closed cross sections, collection and characterization of sediment bed; monitoring of river system, identification of piping classes and mapping urban sprawland sections of Guarapuava intersected by streets. The Cascavel River watershed has about 40% of its area occupied by the urbanization of Guarapuava, of which multiple canals of first-order present headwater areas urbanized and/or semi-urbanized. These canals flow into sub-surfaces, revealing changing not only on specific sections, but also along the longitudinal profile. The surveys revealed that about 30% of the urban fluvial stretches are canalized, with morphological changes that alter the dynamic of the flux. Several enclosed sections overlaid with streets showed accumulation of sediment (technogenic and natural), and of bushes, favoring to reduce the capacity of sections, forming zones of water retention in the events of rain. The percentage of technogenic sediments of bed samples collected in urban areas showed little variation with an average of 18,01%. The surveys of the geometric properties of urban canals showed morphological misfits, with enlargement of urban stretches about three times higher than rural. The data of the flow monitoring showed that the urban area presented a specific flow rate 2.66 times the flow rate of the rural area, what conditions more energy in the flux and maximum flow rates higher leveraging change in the canal geometry and in the occurrence of flooding and urban inundation.